The place of inferior vena cava diameter and proBNP levels indetermining the fluid balance of medical intensive care patients - (:unkn) unknown (My University, 2021)
Objective: Fast and accurate detection of fluid balance in intensive care patients is of special significance. Many different methods areused to determine the fluid balance. In this study, we aimed to determine the fluid balance of patients in the medical intensive careunit using measurement of the inferior vena cava diameter and pro-brain natriuretic peptide (proBNP).Patients and Methods: Patients admitted to the medical intensive care unit between September 2013 and February 2014 were enrolledin the study. Inferior vena cava diameter was measured with a portable ultrasonography, according to guidelines published by theAmerican Echocardiography Association. For pro BNP measurement, samples were taken simultaneously with ultrasonography.Results: One hundred and twenty-six patients (70 male,55.6%) were enrolled for the study. Mean age was 57.8 ± 19.8 (18-89 years).Ninety-six (76.2%) patients were receiving mechanical ventilation support. Mean proBNP levels were 10645.88 ± 12731.08 pg/ml.There was no statistically significant difference between proBNP levels in patients according to the fluid status. Collapsibility indexwas not statistically different according to the volume status (p=0.75).Conclusion: proBNP levels were not correlated with the fluid balance. proBNP levels and inferior vena cava diameters were negativelybut weakly correlated.